Antibacterial activity of probiotics in bladder tumor patients. - Molchanov, R. N. (Medicni Perspektivi, 2014)
The chronic urinary tract infection (UTI) is a risk  factor that worsens a natural course of bladder tumors. Using of probiotics, possessing antagonistic influence on pathogenic microflora and immunocorrection effect, for preventive maintenance and treatment of a chronic UTI in bladder tumor patients is an actual and perspective direction. The goal of the  research was studying antimicrobial  and anti-inflammatory effect  of  a  single bladder instillation of either lactobacilli or aerococci in bladder tumor patients. In the preoperative period a single  bladder instillation with either lactobacterin or a-bacterin preparation to 35 bladder tumor patients was done. Bacteriuria, leucocyturia, lactobacilli and aerococci count in  urine were measured before and in 1, 3, 6 and 24 hours after instillation. Decrease in bacteriuria level in both groups of patients was revealed. Lactobacilli and aerococci count in  urine gradually decreased up to complete elimination in 24 hours (in 1 patient who received lactobacterin (12,5 %) and in 9 patients who received a-bacterin. (40,9 %). Leucocyturia study did not show statistically confidence dynamics throughout the observation period in both groups. Thus, bladder instillation with lactobacterin or a-bacterin leads to suppression of uropathogenic microflora in bladder tumor patients; in the majority of patients spontaneous elimination of lactobacilli and aerococci occurs within 24 hours.